(untitled) (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2024)
Background: Plantar fasciitis (PF) is characterized by inflammation, fibrosis and structural deterioration of foot and there is pain over heel and plantar fascia. Plantar fasciitis pain is gradual in onset, sharp and diffusely located initially which later localizes to medial calcaneal tuberosity. Typically, pain is most severe in the morning which lessens with movement but intensifies with long-standing weight bearing. Plantar fasciitis has been experienced by 10% of the non-athletic population and most typically observed in weight-bearing activities. So, the aim was to study the effects of primal reflex release technique and positional release therapy on pain, functional ability and ankle range in patients with plantar fasciitis. Method: Total 36 patients were recruited for the study as per the selection criteria and were divided into two groups (18 in each group). Group A was treated with primal reflex release technique (PRRT) along with conventional therapy and Group B was treated with positional release therapy (PRT) along with conventional therapy for 7 consecutive days. Intergroup analysis by independent t-test showed statistically significant improvement in pain and functional ability (P value ≤ 0.001). Conclusion: Primal reflex release technique along with conventional therapy was found to be more predominant in improving pain and functional ability than positional release therapy along with conventional therapy. Also, Primal reflex release technique along with conventional therapy and positional release therapy along with conventional therapy were equally effective in improving ankle range of motion.